Sarite cooperative ranch: Cattle growth and production characteristics 1981 and 1982 - Nicholson, M.J. (International Livestock Centre for Africa, 1983)
Analyzes statistically, results of weighings made on two cattle groups at the Sarite cooperative ranch in the southern rangelands of Ethiopia & used as a fattening area to determine effects of place of origin, herdsmen group and sex (bull or castrate) on initial liveweight, weight gain & performance of animals, their purchase & sales prices and profits realised and calculates optimum liveweights at purchase & sale to maximize profits. Includes recommendations on the basis of the results.